PENGARUH DIGITAL MARKETING INSTAGRAM DAN CAFE ATMOSPHERE TERHADAP MINAT KUNJUNGAN PADA CAFE GARTENHUTTE TRAWAS-MOJOKERTO - Teguh Sugiharto; Nersiwad; Kasnowo (Jurnal Cakrawala Ilmiah, 2022)
One of the human needs is the need for refreshment or refreshing. In fulfilling the need for refreshment, it is very necessary which is part of a healthy body to keep oneself in a physically and mentally healthy condition. The cafe that is in great demand today is a cafe with a millennial and contemporary concept with a comfortable atmosphere at a price that is not expensive enough and can be reached by various groups so that it can be used as a means of refreshing and chatting and discussing among young people to stay productive. The atmosphere of the cafe and digital marketing is felt to be able to influence Visiting Interest. This study aims to determine. The Influence of Digital Marketing Instagram, and Cafe Atmosphere on Visiting Interests at Cafe Gartenhutte Trawas-Mojokerto. through the distribution of online questionnaires to consumers. The population in this study are consumers who have an Instagram account and have visited the Gartenhutte Trawas-Mojokerto cafe with a total sample of 386 respondents. The results of the respondent's questionnaire were analyzed using the SPSS 25 application. The results showed that Instagram digital marketing and cafe atmosphere had a positive and significant influence on visiting interest. The results of the simultaneous test state that the independent and dependent variables have an effect on each other.